Influence of the Quality Perceived of Service of a Higher Education Center on the Loyalty of Students - Del Río-Rama, María de la Cruz; Álvarez-García, José; Mun, Nam Kwon; Durán-Sánchez, Amador (Frontiers in Psychology, 2021)
The aim of this research is to validate the explanatory model of how the quality of service perceived by students of a higher education centre influences their loyalty (retaining and attracting new students) through mediating variables: perceived value, expectations and satisfaction. The methodology used to validate the measurement scales is exploratory and confirmatory factor analysis and the Structural Equation Modeling (SEM) technique is applied to analyse the causal relationships proposed in the model. The results show that the key variables to improve student loyalty to the centre are the quality of the service provided and the satisfaction perceived by the students. Both variables are postulated as a major source of competitive advantages. It is also observed that service quality is one of the three key variables to achieve student satisfaction together with expectations and perceived value. This research and its results allow us to understand the relationship between quality and satisfaction with loyalty and to identify the background variables of satisfaction (perceived service quality, perceived value and expectations), as well as to obtain evidence of the importance that expectations have within the model for the formation of both perceived quality and satisfaction.